Ecological niche divergence or ecological niche partitioning in a widespread Neotropical bird lineage - Cooper, Jacob C. (PeerJ, 2024)
Ecological niche divergence is generally considered to be a facet of evolution that may accompany geographic isolation and diversification in allopatry, contributing to species’ evolutionary distinctiveness through time. The null expectation for any two diverging species in geographic isolation is that of niche conservatism, wherein populations do not rapidly shift to or adapt to novel environments. Here, I test ecological niche divergence for a widespread, pan-American lineage, the avian genus of martins (Progne). The genus Progne includes migrant and resident species, as well as geographically restricted taxa and widespread, intercontinentally distributed taxa, thus providing an ideal group in which to study the nature of niche divergence within a broad geographic mosaic. I obtained distributional information for the genus from publicly available databases and created ecological niche models for each species to create pairwise comparisons of environmental space. I combined these data with the most up-to-date phylogeny of Progne currently available to examine the patterns of niche evolution within the genus. I found limited evidence for niche divergence across the breeding distributions of Progne, and much stronger support for niche conservatism with patterns of niche partitioning. The ancestral Progne had a relatively broad ecological niche, like extant basal Progne lineages, and several geographically localized descendant species occupy only portions of this larger ancestral niche. I recovered strong evidence of breeding niche divergence for four of 36 taxon pairs but only one of these divergent pairs involved two widespread species (Southern Martin P. elegans vs. Gray-breasted Martin P. chalybea). Potential niche expansion from the ancestral species was observed in the most wide-ranging present-day species, namely the North American Purple Martin P. subis and P. chalybea. I analyzed populations of P. subis separately, as a microcosm of Progne evolution, and again found only limited evidence of niche divergence. This study adds to the mounting evidence for niche conservatism as a dominant feature of diversifying lineages, and sheds light on the ways in which apparently divergent niches may arise through allopatry while not involving any true niche shifts through evolutionary time. Even taxa that appear unique in terms of habitat or behavior may not be diversifying with respect to their ecological niches, but merely partitioning ancestral niches among descendant taxa.
Keywords: Progne; Ecological niche modeling; Ecological niche partitioning; Niche evolution; Ancestral niche reconstruction; Ecological niche conservatism; Hirundinidae